Two negatives being multiplied DOES equal a positive
In my response to is that is a correct term to answer. <span />
Answer:
x=-1
y=-5
Step-by-step explanation:
(7x+y)-(x+y)=-6
6x=-6
x=-1
-1+y=-6
y=-5
Answer:
You have one algebraic expression. It can be simplified by adding and subtracting like terms within it.
You have two algebraic expressions and are asked to add or subtract them. After adding or subtracting, you’ll end with one final algebraic expression.
the greater common factor is : a.2
141.3 <em>is </em>the nearest tenth. 0.3 is in the tenths place.